A two-dimensional metallosupramolecular framework design based on coordination crosslinking of helical oligoamide nanorods. Issue 5 (6th July 2020) - West, Norton G.; Seoudi, Rania S.; Barlow, Anders J.; Qi, Dongchen; Puskar, Ljiljana; Del Borgo, Mark P.; Kulkarni, Ketav; Adda, Christopher G.; Pan, Jisheng; Aguilar, Marie-Isabel; Perlmutter, Patrick; Mechler, Adam
Abstract : Coordination crosslinking of oligoamide nanorods yields two dimensional metallosupramolecular framework. Abstract : Spontaneous formation of nanostructured materials of defined structure and morphology is a crucial milestone toward realizing true bottom-up nanofabrication. Supramolecular recognition offers unparalleled specificity, selectivity and geometric flexibility to design hierarchical nanostructures. However, competition between similar binding motifs and the dynamic nature of the attachment imposes a severe limitation on the complexity of the achievable structures. Here we outline a design based on two distinct binding motifs in a supramolecular fibrous assembly to realize a metallosupramolecular framework (MSF). Controlled geometries were achieved by one-dimensional supramolecular assembly of substituted oligoamide units. The assembly of the monomers yields nanorods of sub-nanometer diameter and lengths in the 100 μm range. Addition of Cu 2+ led to the formation of well aligned two-dimensional arrays on mica surface. Vibrational spectroscopy confirmed that the backbone amide moieties are not affected by metal addition. XPS and NEXAFS results suggest that Cu(ii ) is reduced in the process to a mixture of Cu(i ) and Cu(0), likely in an interaction with the amine moiety of the imidazole side chain. Our results indicate that the two dimensional superstructure is based on the formation of polynuclear metal complexes between the oligoamide nanorods, thus the structure is confirmed to be a metallosupramolecular framework.